46.9k views
0 votes
Which expression is equivalent to the expression shown below?

-1/2(-3/2x + 6x + 1) - 3x

A) 3/2x - 1/2
B) 6 3/4x - 1/2
C) -3/4x + 1/2
D) -5 1/4x - 1/2

User Rhettg
by
5.1k points

2 Answers

4 votes

The correct answer is: [D]: " (-5 )x − " .

_________________________________________________________

Explanation:

_________________________________________________________

" -1/2(-3/2x + 6x + 1) − 3x " ;

= (-1/2 * -3/2 x) + (-1/2 * 6x) + (-1/2 * 1) − 3x ;

= [ (-1 *-3) /(2*2)] x + (-3x) + (-1/2) ] − 3x ;

= [ (3/4)x − 3x − (1/2) ] − 3x ;

= (3/4)x − 3x − (1/2) − 3x ;

= ?? ; → Combine the "like terms" ;

→ "(3/4)x − 3x − 3x " = ?? ;

→ "(3/4)x − 3x = "(-9/4)x";

→ "(-9/4)x − 3x = "(-21/4)x " = " (-5 )x " ;

→ The answer is: " (-5 )x − " ;

___________________________________________________

→ which is:

___________________________________________________

→ Answer choice: [D]: " (-5 )x − " .

___________________________________________________

User Zdenek
by
4.6k points
0 votes

Answer:

vcbnvjhgbvnhtrgbhj hy6tyuk

Explanation:

User Garzj
by
4.3k points